Perencanaan pembelajaran di sekolah dasar: tinjauan teoretis tentang prinsip, urgensi, dan faktor penentu keberhasilan - Wirayuda, Adnan; Zulfikar, Faizal; Atmaja, Zacky Wiryawan; Iskandar, Sofyan (Universitas Sebelas Maret, 2025)
This article aims to examine the principles, urgency and factors determining the success of learning planning at the elementary school level. The research was carried out using a literature study method with a descriptive qualitative approach, which examined various relevant literature in the field of basic education. The results of the study show that effective learning planning must be based on the principles of clarity of objectives, alignment with educational standards, student-centeredness, and integration of learning theories. The urgency of learning planning lies in its role as a systematic guide for teachers in achieving educational goals, as well as a means of adapting learning strategies to student characteristics. The success factors for learning planning are influenced by internal aspects (teacher competency, mastery of material, creativity, and reflection), external aspects (school environmental support, facilities, and parental involvement), as well as integration between planning and implementation in the classroom. This study emphasizes the importance of increasing teacher capacity and systemic support from schools to ensure optimal learning quality.